Formulation of Endophytic Bacteria in Organic Fertilizer as Health Promoter for Corn Plants in Mentaos, Gudo, Jombang - Arika Purnawati; Tri Mujoko; Endang Triwahyu Prasetyawati (Nusantara Science and Technology Proceedings, 2022)
Corn (Zea mays) has an important role in the food supply in Indonesia, as the second commodity after rice and the second source of carbohydrates after rice which is a derivative of rice and is still considered feasible to meet national needs. The increase in national corn production is strongly supported by several corn production center provinces such as East Java and one of the districts that have the potential to support corn production in East Java is Jombang, but the reality the production experiences several obstacles, one of which is the presence of plant pest organisms (OPT). namely the fungus Peronosclerospora maydis caused by downy mildew. In the control of disease so far in the field, many use fungicides that are harmful to humans and the environment. The solution to reduce the use of fungicides is to utilize endophytic bacteria from eggplant and it has been formulated with organic fertilizer so that it is easier to apply to corn plants, this solution is expected to control disease rates, reduce losses, and improve corn plant health. The method used in community service in Mentaos, Gudo, and Jombang were situation analysis, problem identification, socialization that was attended by 25 farmers, and application of endophytic bacteria from eggplant plants in organic fertilizer formulas. The results obtained are that the people of Mentaos, Gudo, and Jombang were able to apply the endophytic bacterial formula in organic fertilizer with the sprinkle technique. The results show that the community can apply the endophytic bacterial formula, corn plants become healthy, and disease intensity is low.